THE INFLUENCE OF PHOSPHOROUS AND NITROGEN CONTENT IN SOIL ON THE SYMBIOSIS ABILITY OF ARBUSCULAR MYCORRHIZAS FUNGI IN THE HOST PLANT ROOT, AND THE EFFECT OF LEAD REMOVAL FROM SOIL BY MAIZE - Cường, Bùi Văn; Chính, Tăng Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY The study was conducted to investigate how the nutrient factor in soil (Phosphorous and Nitrogen) influence on the symbiosis ability of arbuscular mycorrhizas fungi to the host plant, and the effect of lead (Pb) removal from soil by maize. The results showed that, AM fungi were inhibited to penetrate into maize root when they were cultured in rich nutrient soil. In the soil with low concentration of nitrogen and phosphorus nutrient (formula TN1), the density of AM fungi was three times higher than this in high nutrient soil (formula TN8), and the amount of Pb accumulate in maize biomass of TN1 was also the highest in all formulas. However, the treatment effect of TN1 formula did not get the optimal value, because the total amount of biomass was the lowest in comparison with the other formulas. Formula TN5 gained the optimal value of treatment process, since they could remove the highest amount of lead out from the soil. The concentration of phosphorus and nitrogen in formula TN5 were 752.5 ppm and 87.6 ppm, so they did not prevent AM fungi from inoculating maize root, and they were not too low for maize to achieve high biomass.